Systemic Kikuchi-Fujimoto disease bordering lupus lymphadenitis: A fresh look? - Behdadnia, Aram (Intractable Rare Dis Res, 2016)
A 31-year old woman with persistent fever for 6 weeks and unresponsive to antibiotic therapy came for rheumatologic investigation. After computed tomography (CT) studies of her neck, thorax and abdomen revealed bilateral cervical, axillary and retroperitoneal lymph node enlargements, histopathologic evaluation of the resected nodes showed features of histiocytic necrotizing lymphadenopathy suggestive of Kikuchi-Fujimoto's lymphadenopathy. Kikuchi-Fujimoto Disease (KFD) involving the retroperitoneal nodes is extremely unusual and even more challenging to diagnose when there are no early signs of extranodal involvement or abdominopelvic pain. We present a case of systemic KFD involving the cervical, axillary and retroperitoneal lymph nodes and emphasize the clinical interest to properly differentiate between the benign condition of KFD that requires no more than minimal to low dosage steroid therapy and the potentially life-threatening lupus lymphadenitis that mandates intensive immunosuppressive treatment.